The stochastic transition from size dependent to size independent yield strength in metallic glasses. (December 2017) - Li, F.C.; Wang, S.; He, Q.F.; Zhang, H.; Sun, B.A.; Lu, Y.; Yang, Y.
Abstract: It has been an enduring and heated debate whether the yield strength of metallic glasses (MGs) is size dependent or size independent. In this work, we first develop a micromechanical model by taking into account the stochasticity for shear band initiation in microcompression. Our modeling is subsequently verified through the extensive in-situ and ex-situ microcompression experiments. Through the efforts of combined experiments and modeling, we show a size-controlled stochastic transition from the size dependent to the size independent yield strength in the MG micropillars. Such a stochastic transition is featured with a strong fluctuation in the measured yield strengths when the micropillar size is near an intrinsic length scale which varies with the chemical composition of MGs. In contrast, such a size-controlled transition appear deterministic with little data scattering in tension. At the fundamental level, our results unfold a size dependent shear band initiation process in MGs, which may be applicable to other amorphous materials of technological importance. Graphic abstract: Image, graphical abstract